Strategi Peningkatan Minat dan Mental Wirausaha pada Siswa SDN Nagrak 05 untuk Mewujudkan Generasi Pengusaha Sukses di Masa Depan - Son Haji; Putri Ayu Tamara; Septi Rizkiani; Oktaviarni Oktaviarni; Muhammad Rizqi Nurpratama; Olla Violetta Shakira; Alfian Nul Haki; Elfita Aprilia (FKIP, Universitas Palangka Raya, 2025)
Entrepreneurship education is an important aspect in shaping the character and skills of the younger generation to face future challenges. The aim of this service is to increase interest and entrepreneurial mentality among students at SDN Nagrak 05 through counseling, training and mentoring. This program is designed to foster students' self-confidence and awareness regarding the importance of entrepreneurship as a potential career choice and equip them with the basic skills for making handicrafts and making food to become successful entrepreneurs. The methods used are practice-based training, motivation through sharing sessions, as well as simulations and introductions to the business world with a fun approach. This program involves collaboration between students, teachers and parents in supporting the development of students' entrepreneurial interests and mentality. The expected result of this activity is an increase in students' knowledge about entrepreneurship, as well as the development of a tough and creative mental attitude in facing various challenges. Evaluation is carried out through observations and interviews to measure changes in students' attitudes and interests regarding entrepreneurship. It is hoped that this program can contribute to creating a young generation who has the readiness and courage to start a business early, and is able to adapt to face global economic dynamics